Adhesive composition for decorative sheets, decorative sheet, decorative structure, and manufacturing method thereof

JP2025031462APending Publication Date: 2025-03-07TOYO INK MFG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023220346
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0015】 本発明により、成形品の加飾において、加熱前の貼り直し性や凹凸追従性、高温または高温高湿下での耐久性、成形品に優れた外観を付与でき、かつ凹凸追従性に優れる、加飾シート用粘着剤組成物、加飾シート、加飾構造体およびその製造方法の提供をすることが可能となる。 所定の(メタ)アクリレートを含む(メタ)アクリル酸エステル共重合体(A)と硬化剤(B)を含有する粘着剤組成物で粘着剤層を形成するとき、加熱前の貼り直し性や高温 または高温高湿環境下での耐久性、優れた外観、凹凸追従性といった各性能を高度に両立させることができることを知得した。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031462000001
    Figure 2025031462000001
  • Figure 2025031462000002
    Figure 2025031462000002
  • Figure 2025031462000003
    Figure 2025031462000003
Patent Text Reader

Abstract

To provide an adhesive composition for a decorative sheet, a decorative sheet, a decorative structure, and a manufacturing method thereof, which are used for attaching to an adherend by a vacuum forming method or a vacuum and pressure forming method, and which allow repositioning before heating, realize durability under high-temperature or high-temperature and high-humidity conditions, follow surface irregularities, and can impart an excellent appearance to a molded product.SOLUTION: The adhesive composition for a decorative sheet used for attaching to an adherend by a vacuum forming method or a vacuum and pressure forming method comprises: (A) a (meth)acrylate copolymer that is a copolymer of a monomer mixture containing respective specific amounts of (a) an alkyl (meth)acrylate monomer where an alkyl group has 8 carbon atoms and (b) a monomer having a carboxyl group; and (B) a curing agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition for a decorative sheet used for attachment to an adherend by vacuum forming or vacuum / pressure forming, a decorative sheet, a decorative structure, and a method for producing the same. [Background technology]

[0002] Decorating the exterior surface of molded products such as automobile interior and exterior parts, keyboards, home appliances, smartphones, housing materials, furniture, musical instruments, and Shinkansen window frames and walls is being done with decorative films (decorative sheets) to improve the appearance quality of the molded products. Methods for decorating molded products with three-dimensional shapes using decorative sheets include insert molding, in-mold molding, vacuum molding, and vacuum-compressed air molding.

[0003] The insert molding method is a method in which a decorative sheet is first formed into a specified shape and inserted into a mold, and then heated molten resin is pressurized and poured into the mold for injection molding, and then cooled and solidified to produce a decorated molded product in which the decorative sheet and the molded product are integrated. In-mold molding is a method of producing a decorated molded product by setting a film with a printed design in a mold with a release layer between them, injecting heated molten resin and allowing it to cool and solidify, and then peeling off the film to transfer the design. In this way, in the insert molding method and the in-mold molding method, the molded article is decorated at the same time as it is molded, and a design is formed on the exterior surface of the molded article.

[0004] On the other hand, vacuum forming is a method in which the decorative sheet is softened by applying heat and the air between the decorative sheet and the molded product is removed from the molded product side, creating a near-vacuum state and adhering the decorative sheet to the molded product. In addition, the vacuum and pressure molding method creates a similar vacuum state, and then applies air pressure from the decorative sheet side above the molded product to adhere the decorative sheet to the molded product. Thus, the vacuum forming method and the vacuum pressure forming method are methods for decorating a molded product by attaching a decorative sheet at room temperature after the molded product is completed and heating it. In other words, the decorative sheet is attached to the exterior surface of the molded product in a separate operation from the molding of the molded product, so that a single device can be used to attach the decorative sheet to molded products of various shapes. In addition, the vacuum forming method and the vacuum pressure forming method are widely used because they allow continuous coating from the front to the back of the molded product edge, i.e., wrap-around coating, which is difficult to achieve with the in-mold molding method and the like.

[0005] Patent Document 1 discloses a molded article obtained by bonding, by heat and pressure, an adhesive film having an adhesive layer containing a (meth)acrylic polymer containing carboxy groups in a specific ratio and having a glass transition temperature of 25°C or lower, and a (meth)acrylic polymer containing amino groups in a specific ratio and having a glass transition temperature of 75°C or higher.

[0006] Patent Document 2 discloses a pressure-sensitive adhesive composition containing two types of (meth)acrylic polymers having glass transition temperatures in a specific range in a specific ratio.

[0007] Patent Document 3 discloses a decorative molding film including an adhesive layer, which is characterized by containing a copolymer of methyl acrylate and an alkyl acrylate ester containing an alkoxy group having four carbon atoms, and 1 to 40 parts by weight of an alkyl (meth)acrylate ester having a glass transition temperature of 115°C or lower and a weight average molecular weight of 5,000 to 100,000 per 100 parts by weight of the copolymer. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2009-035588 A [Patent Document 2] International Publication No. 2021 / 049480 [Patent Document 3] JP 2017-132205 A Summary of the Invention [Problem to be solved by the invention]

[0009] Usually, when a decorative sheet is attached to a molded product by vacuum molding or vacuum-pressure molding, it is often reattached before molding because it cannot be reattached after heat molding. Therefore, it is essential that it can be easily reattached. In addition, since a three-dimensional decorated molded product is expected to be used in various environments, it is important that it conforms to a complex shape having curved surfaces and uneven parts, and that it has durability that does not cause poor appearance such as lifting or peeling at the adhesive interface with the adhesive layer even in high temperature or high temperature and high humidity environments, and there is a demand for a pressure-sensitive adhesive composition for a decorative sheet that can satisfy each of these performances in a well-balanced manner.

[0010] Although the adhesive layer described in Patent Document 1 has excellent adhesion at high temperatures, it has a high glass transition temperature, and therefore has a problem in that the decorative sheet cannot be temporarily attached to the substrate before vacuum forming or vacuum-pressure forming.

[0011] The pressure-sensitive adhesive composition of Patent Document 2 has excellent repositionability and coating film appearance, but does not mention durability in high-temperature environments, and is therefore insufficient in terms of practical performance.

[0012] The decorative molding film of Patent Document 3 achieves adhesion, dimensional stability, and conformability to curved surfaces up to an environment of 80°C, but in high-temperature environments of 100°C or above, or when attached to more complex uneven surfaces, lifting or peeling occurs, resulting in poor appearance.

[0013] That is, no pressure-sensitive adhesive composition for decorative sheets has been developed to date that is capable of providing excellent repositionability before heating, durability at high temperatures or high temperature and high humidity, ability to conform to irregularities, and excellent appearance to molded articles. [Means for solving the problem]

[0014] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. That is, the adhesive composition is characterized in that it contains a (meth)acrylic acid ester copolymer (A) and a curing agent (B), the (meth)acrylic acid ester copolymer (A) is a copolymer of a monomer mixture, the monomer mixture contains a (meth)acrylic acid alkyl ester monomer (a) having an alkyl group with 8 carbon atoms and a monomer (b) having at least one type of carboxy group, the content of the (meth)acrylic acid alkyl ester monomer (a) having an alkyl group with 8 carbon atoms is 50 to 98 mass% in 100 mass% of the monomer mixture, and the content of the monomer (b) having a carboxy group is more than 0 mass% and less than 12 mass% in 100 mass% of the monomer mixture. Effect of the Invention

[0015] The present invention makes it possible to provide a pressure-sensitive adhesive composition for decorative sheets, decorative sheets, and decorative structures, which are excellent in repositionability before heating, in conformity with irregularities, in durability at high temperatures or high temperatures and high humidity, and in appearance to molded articles, and which are also excellent in conformity with irregularities, as well as a method for producing the same, in decorating molded articles. When forming an adhesive layer from an adhesive composition containing a (meth)acrylic acid ester copolymer (A) containing a specific (meth)acrylate and a curing agent (B), the repositionability before heating and the curing property at high temperatures are The inventors also discovered that it is possible to achieve a high degree of compatibility between various performance characteristics, such as durability in high-temperature and high-humidity environments, excellent appearance, and ability to conform to uneven surfaces. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The pressure-sensitive adhesive composition for decorative sheets, the decorative sheet, the decorative structure, and the method for producing a decorative structure according to the present disclosure have the following configurations [1] to [7]. [1] A composition comprising a (meth)acrylic acid ester copolymer (A) and a curing agent (B), The (meth)acrylic acid ester copolymer (A) is a copolymer of a monomer mixture, The monomer mixture contains a (meth)acrylic acid alkyl ester monomer (a) having an alkyl group with 8 carbon atoms and a monomer (b) having at least one type of carboxy group, and is characterized in that the content of the (meth)acrylic acid alkyl ester monomer (a) having an alkyl group with 8 carbon atoms is 50 to 98 mass% in 100 mass% of the monomer mixture, and the content of the monomer (b) having a carboxy group is more than 0 mass% and less than 12 mass% in 100 mass% of the monomer mixture. A pressure-sensitive adhesive composition for decorative sheets used for attachment to an adherend by vacuum forming or vacuum / pressure forming. [2] The pressure-sensitive adhesive composition for decorative sheets according to [1], wherein the curing agent (B) is an epoxy-based curing agent. [3] The adhesive composition for decorative sheets according to [1] or [2], characterized in that the monomer mixture further contains at least one of (c) a (meth)acrylic acid alkyl ester monomer having 1 to 3 alkyl carbon atoms and (d) a (meth)acrylic acid alkyl ester monomer having 4 alkyl carbon atoms and having a glass transition temperature of -30°C or higher when the homopolymer is polymerized, the total content of which is 1 to 45 mass% in 100 mass% of the monomer mixture. [4] A decorative sheet comprising a substrate and an adhesive layer made of the adhesive composition for decorative sheets according to any one of [1] to [3]. [5] A decorative structure comprising an adherend and the decorative sheet according to [4]. [6] A method for producing a decorative structure according to [5], characterized in that the decorative sheet is integrated with an adherend by vacuum forming or vacuum-pressure forming to form a decorative structure.

[0017] The present disclosure will be described in detail below. It should be noted that other embodiments are of course included in the scope of the present disclosure as long as they conform to the spirit of the present disclosure.

[0018] In the present disclosure, the term "sheet" refers to a flexible laminate, and includes a thin laminate called a "film."

[0019] In the present disclosure, "(meth)acrylic" means either or both of "acrylic" and "methacrylic", and "(meth)acrylate" means either or both of "acrylate" and "methacrylate".

[0020] In this disclosure, a numerical range specified using "~" is intended to include the numerical values ​​before and after "~" as the lower and upper limit values ​​of the range.

[0021] In this disclosure, "Mw" is the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC), and "Mn" is the number average molecular weight in terms of polystyrene measured by GPC. The weight average molecular weight and number average molecular weight can be measured by the method described in the section [Examples].

[0022] In the present disclosure, "(meth)acrylic acid alkyl ester having an alkyl group with 8 carbon atoms" "Monomer (a)" may be abbreviated as "monomer (a)", "monomer (b) having a carboxy group" may be abbreviated as "monomer (b)", "(meth)acrylic acid alkyl ester monomer (c) having 1 to 3 alkyl carbon atoms" may be abbreviated as "monomer (c)", and "(meth)acrylic acid alkyl ester monomer (d) having a homopolymer glass transition temperature of -30°C or higher and having 4 alkyl carbon atoms" may be abbreviated as "monomer (d)".

[0023] In addition, the following describes in detail the embodiments of the present invention, but the following description is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.

[0024] <Adhesive composition> The pressure-sensitive adhesive composition comprises a (meth)acrylic acid ester copolymer (A) and a curing agent (B), the (meth)acrylic acid ester copolymer (A) being a copolymer of a monomer mixture, the monomer mixture containing a (meth)acrylic acid alkyl ester monomer (a) having an alkyl group with 8 carbon atoms and a monomer (b) having a carboxy group, the content of the (meth)acrylic acid ester monomer (a) having an alkyl group with 8 carbon atoms being 50 to 98 mass% in 100 mass% of the monomer mixture, and the content of the monomer (b) having a carboxy group being greater than 0 mass% and less than 12 mass% in 100 mass% of the monomer mixture.

[0025] <(Meth)acrylic acid ester copolymer (A)> The (meth)acrylic acid ester copolymer (A) contained in the present pressure-sensitive adhesive composition (hereinafter also referred to as copolymer (A)) is a copolymer obtained by polymerizing all or a part of a mixture of monomers containing a (meth)acrylic acid ester.

[0026] In 100% by mass of the monomer mixture, the content of the (meth)acrylic acid alkyl ester monomer (a) having an alkyl group with 8 carbon atoms is 50 to 98% by mass, more preferably 55 to 80% by mass, and particularly preferably 60% by mass or more and less than 70% by mass. By keeping it within the above range, excellent unevenness-following ability, durability under high temperature and high humidity, and repositionability can be imparted.

[0027] Examples of the monomer (a) include 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and normal octyl (meth)acrylate. These may be used alone or in combination of two or more. Among them, those having an alkyl group with a branched structure are preferred, and 2-ethylhexyl (meth)acrylate is particularly preferred from the viewpoint of conformability to uneven surfaces.

[0028] In 100% by mass of the monomer mixture, the content of the monomer (b) having a carboxyl group is more than 0% by mass and less than 12% by mass, more preferably less than 10% by mass, even more preferably 6% by mass or less, and particularly preferably less than 5% by mass. The lower limit is preferably 1% by mass or more. By keeping it within the above range, it is possible to achieve a high degree of compatibility between adhesive strength, durability in high temperature or high temperature and high humidity environments, and repositionability.

[0029] Examples of the monomer (b) include (meth)acrylic acid, 2-carboxyethyl acrylate, itaconic acid, maleic acid, styrenesulfonic acid, 2-(meth)acryloyloxyethyl-succinic acid, 2-(meth)acryloyloxyethyl-phthalic acid, and 2-acryloyloxyethylhexahydrophthalic acid. These may be used alone or in combination of two or more. Among them, (meth)acrylic acid and 2-carboxyethyl acrylate are preferred from the viewpoint of polymerizability.

[0030] Compatibility with other components, dispersibility of other components, adhesion to substrates and adherends, crosslinkability, etc. Depending on the purpose of adjusting the amount of the monomer, other monomers than the monomers (a) and (b) can also be used in the synthesis of the copolymer (A). More specifically, in the present invention, the monomer mixture constituting the copolymer (A) preferably further contains at least one of (c) a (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 3 carbon atoms and (d) a (meth)acrylic acid alkyl ester monomer having an alkyl group with 4 carbon atoms and having a glass transition temperature of -30°C or higher of the homopolymer.

[0031] Examples of the monomer (c) include methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate. Examples of the monomer (d) include n-butyl methacrylate (Tg: 20°C), isobutyl acrylate (Tg: -26°C), isobutyl methacrylate (Tg: 48°C), tert-butyl acrylate (Tg: 14°C), and tert-butyl methacrylate (Tg: 107°C). These may be used alone or in combination of two or more. Among them, from the viewpoints of curved surface properties, repositionability, and unevenness-following properties, monomer (c) is preferred, and methyl (meth)acrylate and ethyl (meth)acrylate are particularly preferred.

[0032] In 100% by mass of the monomer mixture, the total content of monomer (c) and monomer (d) is preferably 1 to 45% by mass, more preferably 11 to 40% by mass, and particularly preferably 15 to 35% by mass. By keeping it within the above range, durability in high temperature and high temperature / high humidity environments can be improved.

[0033] In the present invention, the glass transition temperature (Tg) of the copolymer (A) is a value calculated based on the following formula (1) (Fox formula). 1 / Tg=W1 / Tg1+W2 / Tg2+ +Wn / Tgn (Formula 1) [In formula (1), Tg is the Tg (unit: K) of the acrylic polymer (A), Tgi (i = 1, 2, ... n) is the Tg (unit: K) when the radical polymerizable monomer i forms a homopolymer, and Wi (i = 1, 2, ... n) is the mass fraction of the radical polymerizable monomer i in all monomer components. For the Tg of the homopolymer, published values ​​such as literature values ​​and catalog values ​​are used.] The above formula (1) is a calculation formula when the copolymer (A) is composed of n types of monomer components, namely, monomer 1, monomer 2, . . . , monomer n.

[0034] Further, examples of other monomers that can be contained in the monomer mixture constituting the copolymer (A) include the following.

[0035] Vinyl monomers such as vinyl acetate, vinyl propionate, styrene, vinyl laurate, vinyl caprate, vinyl caprylate, and vinyl nonanoate; (meth)acrylic acid alkyl ester monomers having an alkyl group having 4 to 26 carbon atoms, such as n-butyl acrylate, (meth)acrylic acid, isopentyl (meth)acrylate, 2-methylbutyl (meth)acrylate, 4-methyl-2-pentyl (meth)acrylate, heptyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, eicosanyl (meth)acrylate, and hexacosanyl (meth)acrylate (excluding (meth)acrylic acid ester monomers (a) and (d)); (Meth)acrylate, Cyclohexyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate (meth)acrylic acid ester monomers having an aliphatic ring, such as isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and 3,3,5-trimethylcyclohexyl (meth)acrylate; (meth)acrylic acid ester monomers having an aromatic ring, such as benzyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 2-(o-phenylphenoxy)ethyl (meth)acrylate, and nonylphenoxy polyethylene glycol (meth)acrylate; (meth)acrylic acid ester monomers having an alkoxy group, such as 2-methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate; (meth)acrylic acid ester monomers having a polyether chain, such as methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, and phenoxypolypropylene glycol (meth)acrylate; N-vinyl cyclic amide monomers such as N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione; (meth)acrylamide-based monomers such as (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide, N-hydroxyalkyl(meth)acrylamide, and N-alkoxyalkyl(meth)acrylamide; N,N-dialkyl(meth)acrylamide monomers such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide; N-hydroxyalkyl (meth)acrylamide monomers such as N-methylol (meth)acrylamide, N-(2)-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-2-hydroxyethyl (meth)acrylamide; N-alkoxyalkyl(meth)acrylamides such as N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide; Monomers having an acidic group other than a carboxy group, such as 2-(meth)acryloyloxyethyl acid phosphate and 2-methacryloyloxyethyl acid phosphate; Examples of the monomer include (meth)acrylic acid ester monomers having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and polyalkylene glycol mono(meth)acrylate, as well as allyl ether monomers having a hydroxyl group, such as polyalkylene glycol allyl ether. These may or may not be contained in the monomer mixture constituting the copolymer (A) as required.

[0036] The content of the other monomers is not particularly limited, but is preferably from 0% by mass to 30% by mass in terms of adhesive strength.

[0037] The polymerization form of the (meth)acrylic acid ester copolymer (A) is not particularly limited. That is, the copolymer (A) may be any of an alternating copolymer, a random copolymer, a block copolymer, and a graft copolymer of each monomer including a (meth)acrylic acid alkyl ester. For example, the block copolymer may be a diblock or a triblock.

[0038] The copolymer (A) can be synthesized by a conventionally known method, for example, by a known polymerization method such as a solution polymerization method, a bulk polymerization method, an emulsion polymerization method, or a suspension polymerization method. The copolymer (A) can be synthesized by a known polymerization method such as a living radical polymerization method or an active energy ray polymerization method. In this case, the monomer mixture for synthesizing the copolymer (A) can contain a photopolymerization initiator or a conventionally known additive. As the active energy ray, ultraviolet light, visible light, X-rays, gamma rays, or electron beams can be used. In addition, light sources such as a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a metal halide lamp, an electrodeless lamp, and an LED can be used for irradiation with ultraviolet light.

[0039] The blending ratio of each structural unit (monomer component) of the copolymer (A) can be determined using various instruments such as nuclear magnetic resonance analysis (NMR) and gas chromatography (GC).

[0040] The weight average molecular weight (Mw) of the (meth)acrylic acid ester copolymer (A) is preferably 600,000 to 2,000,000, more preferably 800,000 to 1,600,000, and even more preferably more than 1,000,000 to 1,500,000. When the Mw of the copolymer (A) is within the above range, sufficient durability can be obtained.

[0041] <Hardening agent (B)> This composition contains a curing agent (B). By providing a crosslinking group to the (meth)acrylic acid ester copolymer (A) and crosslinking it with the curing agent (B), the cohesive strength, adhesive strength, and durability at high temperatures or high temperature and high humidity of the adhesive layer can be improved.

[0042] Examples of the curing agent contained in the pressure-sensitive adhesive composition include isocyanate-based curing agents, epoxy-based curing agents, aziridine-based curing agents, metal chelate-based curing agents, amine-based curing agents, acrylate-based curing agents, etc. Among these, isocyanate-based curing agents, epoxy-based curing agents, and metal chelate-based curing agents are preferred, and epoxy-based curing agents and metal chelate-based curing agents are more preferred from the viewpoint of repositionability, and epoxy-based curing agents are particularly preferred from the viewpoint of durability in high-temperature environments. It is preferable to use one type of curing agent alone.

[0043] Examples of the isocyanate-based curing agent include compounds having three or more isocyanate groups in the molecule, such as adducts of diisocyanates such as tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate with polyol compounds such as trimethylolpropane, as well as biuret forms and isocyanurates thereof, and adducts of the above diisocyanates with any one of polyols such as polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and polyisoprene polyols; Examples of the isocyanate include diisocyanates such as hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethyl xylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate, as well as compounds having two isocyanate groups in the molecule such as allophanate bodies of hexamethylene diisocyanate. Among these, trimethylolpropane adducts of tolylene diisocyanate are preferred because they can easily adjust the adhesive properties. The number of isocyanate groups is the average number.

[0044] Examples of epoxy curing agents include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane. From the viewpoint of curability and durability, N,N,N',N'-tetraglycidyl-m-xylylenediamine and 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane are particularly preferred.

[0045] Examples of the aziridine-based curing agent include β-aziridinyl propionate, trimethylolpropane tris(β-aziridinyl propionate), etc. In addition, examples of commercially available products include “TAZO” and “TAZM” manufactured by Sogo Pharmaceutical Co., Ltd., and “ChemiTite PZ-33” manufactured by Nippon Shokubai Co., Ltd.

[0046] Examples of the metal chelate curing agent include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium and zirconium with acetylacetone or ethyl acetoacetate.

[0047] Examples of the amine-based curing agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetramine, diethylenetriamine, triethyltetramine, isophoronediamine, amino resins, and methylene resins.

[0048] Examples of the acrylate-based curing agent include polyfunctional acrylates such as 1,6-hexanediol acrylate.

[0049] The content of the curing agent (B) may be appropriately changed depending on the desired physical properties such as the type and degree of crosslinking of the copolymer (A), but from the viewpoints of adhesive strength, repositionability, and durability at high temperatures, it is preferably 0.01 to 3 parts by mass, more preferably 0.015 to 1 part by mass, even more preferably 0.018 to 0.5 parts by mass or less, and particularly preferably 0.02 to 0.06 parts by mass, relative to 100 parts by mass of the copolymer (A). In particular, by setting the content of the epoxy compound as the curing agent within the above range, it is possible to achieve a high degree of both adhesion and heat resistance in a high-temperature environment.

[0050] The degree of crosslinking of the pressure-sensitive adhesive composition of the present invention is indicated by the gel fraction, and the method for measuring it is as shown in the Examples. The gel fraction is not particularly limited, but is preferably 40 to 70%, and particularly preferably 50 to 60%. By setting it within the above range, it is possible to achieve a high degree of both repositionability and durability in a high-temperature environment.

[0051] <Organic solvent (C)> The pressure-sensitive adhesive composition may contain an organic solvent (C). By containing the organic solvent (C), the pressure-sensitive adhesive composition can be easily adjusted to a suitable viscosity for application to an object to be applied, and the application property can be improved. In addition, in general, in an ultraviolet curing system in which a pressure-sensitive adhesive composition is applied and cured without a solvent, the degree of crosslinking in the coating film tends to be non-uniform due to oxygen inhibition, the distance from the ultraviolet lamp, etc., whereas in a thermosetting system containing an organic solvent (C), a crosslinking reaction occurs uniformly in the coating film, and therefore it is possible to easily achieve properties such as unevenness-following ability. As the organic solvent (C), the solvent used in the polymerization of the (meth)acrylic acid ester copolymer (A) may be used as it is, or a further solvent may be added, and any suitable solvent may be used.

[0052] Examples of the organic solvent (C) include methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, xylene, hexane, acetone, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, n-propanol, and isopropanol. These may be used alone or in combination of two or more. The viscosity of the adhesive composition can be adjusted by adding these organic solvents, or the viscosity can be reduced by heating the adhesive composition. From the viewpoint of solubility and drying property, it is preferable to use an organic solvent having an SP value of 9 or more. Examples of organic solvents having an SP value of 9 or more include ethyl acetate, butyl acetate, methyl ethyl ketone, isopropanol, etc. Among these, it is more preferable to use ethyl acetate. On the other hand, from the viewpoint of decreasing the viscosity of the pressure-sensitive adhesive composition, it is preferable to use an organic solvent having an SP value of less than 9. Examples of organic solvents having an SP value of less than 9 include hexane, heptane, and octane.

[0053] In addition to the copolymer (A) and the curing agent (B), the pressure-sensitive adhesive composition may contain, as necessary, any additives such as a tackifier, a resin other than the copolymer (A), a plasticizer, a silane coupling agent, a leveling agent, inorganic and / or organic fine particles, an ultraviolet absorber, a light stabilizer, an antioxidant, etc. The amount of these additives added can be appropriately selected within a range in which the effects of the present disclosure can be obtained, and for example, it is preferable to appropriately set the content of the copolymer (A) within the above range.

[0054] Resins other than the (meth)acrylic acid ester copolymer (A) include known thermoplastic resins, such as low-density polyethylene, very low-density polyethylene, low-crystalline (amorphous) polypropylene, ionomer resins, ethylene copolymers such as ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylic acid ester-maleic anhydride copolymers, and ethylene-glycidyl methacrylate copolymers, as well as olefin-based copolymers such as polyolefin-modified polymers, as well as thermoplastic elastomers such as butadiene-based elastomers, ester-based elastomers, styrene-based elastomers, styrene-butadiene-based elastomers, styrene-isoprene-based elastomers, and polyurethane-based elastomers, as well as thermoplastic polyesters, as well as polyamide-based resins such as polyamide-based copolymers, polyurethanes, polystyrene-based resins, cellophane, polyacrylonitrile, and polyvinyl chloride-based resins such as vinyl chloride-vinyl acetate copolymers, etc. These resins may be used alone or in combination of two or more. The content of these other resins in the solid content of the composition is preferably less than 10% by mass. If the content of these resins is less than 10% by mass, good compatibility is easily obtained, and appropriate adhesive strength can be easily obtained.

[0055] In order to adjust the adhesive strength, a tackifier (tackifier resin) can be used in the present adhesive composition. The tackifier is not particularly limited, but examples thereof include rosin-based resins, terpene-based resins, synthetic hydrocarbon-based resins, etc.

[0056] Examples of rosin-based resins include rosin ester, polymerized rosin, hydrogenated rosin, disproportionated rosin, maleic acid modified rosin, fumaric acid modified rosin, rosin phenolic resin, and natural rosin.

[0057] Examples of terpene resins include α-pinene resins, β-pinene resins, dipentene resins, aromatic modified terpene resins, hydrogenated terpene resins, terpene phenol resins, acid modified terpene resins, styrenated terpene resins, and styrene-aliphatic hydrocarbon copolymer resins.

[0058] Examples of synthetic hydrocarbon resins include coumarone resins, coumarone-indene resins, styrene resins, xylene resins, phenol resins, and petroleum resins.

[0059] From the viewpoint of obtaining a good adhesive strength to the object to be affixed, it is preferable to use a rosin-based resin or a terpene-based resin as the tackifier. The tackifier may be used alone or in combination of two or more kinds.

[0060] The content of the tackifier is preferably less than 30 parts by mass, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, based on 100 parts by mass of the acrylic acid ester copolymer (A). By making the content of the tackifier less than 30 parts by mass, it is easy to obtain good compatibility, appropriate re-tensioning property, and excellent appearance of the molded product.

[0061] The pressure-sensitive adhesive composition preferably contains the (meth)acrylic acid ester copolymer (A) as a main component, which refers to the component that is present in the greatest amount among all the components contained in the target object (here, the composition). Specifically, the content of the (meth)acrylic acid ester copolymer (A) in 100% by mass of the solid content of the present adhesive composition is preferably 70 to 100% by mass, more preferably 80 to 100% by mass, and even more preferably 90 to 99% by mass. When the (meth)acrylic acid ester copolymer (A) is contained in 70% by mass or more in 100% by mass of the solid content of the present adhesive composition, it is possible to easily obtain an appropriate adhesive strength that allows repositioning at room temperature and is free of air bubble entrapment and foreign matter contamination.

[0062] <Decorative sheet> The present adhesive composition described above can be preferably used for a decorative sheet. The decorative sheet according to the present invention (hereinafter also referred to as the present decorative sheet) comprises a substrate and an adhesive layer made of a cured product of the present adhesive composition. If necessary, the exposed surface of the adhesive layer can be covered with a release sheet. The release sheet is peeled off when the adhesive sheet is attached to an adherend. The substrate is not particularly limited, and examples thereof include resin sheets, paper, and metal foils. The substrate may be a laminated sheet in which any one or more layers are laminated on at least one surface of the substrate. The surface of the substrate on which any adhesive layer is formed may be subjected to an easy-adhesion treatment such as corona discharge treatment and application of an anchor coating agent, if necessary. The release sheet is not particularly limited, and any known release sheet can be used, which is obtained by subjecting the surface of a base sheet such as a resin sheet or paper to a known release treatment such as coating with a release agent.

[0063] The method for producing the present decorative sheet having an adhesive layer can be appropriately used by a conventionally known method, and is not particularly limited. For example, the present composition, which is diluted with a solvent as necessary, is coated on a sheet on which a surface layer and a decorative layer are formed by knife coating, bar coating, blade coating, doctor coating, roll coating, cast coating, etc. to form a coating film. Then, the adhesive layer (solidified material) can be formed on the sheet by heating and drying or curing as necessary. In addition, when the copolymer (A) contained in the present composition needs to be crosslinked by active energy rays, the present composition is applied onto a sheet, and then the sheet is irradiated with active energy rays to form a pressure-sensitive adhesive layer (crosslinked product). In this case, for example, a belt conveyor type ultraviolet ray irradiation device is used to irradiate the pressure-sensitive adhesive composition applied onto the sheet with ultraviolet rays to obtain a pressure-sensitive adhesive layer. The ultraviolet ray irradiation dose is, for example, 500 mJ / cm. 2 That's it, 5 000mJ / cm 2 It can be as follows: This decorative sheet has a moderate adhesive strength at room temperature (e.g., 25°C), has excellent adhesiveness when bonded at high temperatures (e.g., 100 to 130°C), and can maintain its properties for a long period of time at high temperatures (e.g., 100°C for 7 days). Therefore, this decorative sheet can be applied to the decoration of aircraft, automobiles, interior and exterior of building materials, nursing and medical fields, electrical appliances, electronic parts, smartphones, furniture, musical instruments, Shinkansen window frame walls, etc., by three-dimensional surface decoration (Three Dimension Overlay Method: TOM molding), which is a type of vacuum and compressed air molding.

[0064] <Decorative structure and method for producing same> The decorative structure according to the present disclosure (hereinafter also referred to as the present structure) can be formed by attaching a decorative sheet to an adherend using the present pressure-sensitive adhesive composition. The adherend is not particularly limited, and various shapes of objects (e.g., molded products having three-dimensional shapes) can be used. The decorative sheet using the present pressure-sensitive adhesive composition is used for attachment to an adherend by a vacuum forming method and a vacuum-pressure forming method. Conventionally known methods can be appropriately applied for the vacuum forming method and the vacuum-pressure forming method.

[0065] More specifically, the present decorated structure can include, for example, a surface layer, a decorative layer, and a pressure-sensitive adhesive layer in this order. The surface layer is a layer that becomes the surface of the decorated molded product, and any layer that is conventionally known in the field of decorative sheets can be used as appropriate. The surface layer can be made of various resins, such as acrylic resin, polyurethane, fluororesin, and polyvinyl chloride. The exposed surface of the surface layer may also be embossed. The decorative layer is for decorating the object to be decorated, and various materials can be used depending on the intended use. The decorative layer can contain at least one resin selected from the group consisting of olefin resins, styrene resins, and vinyl chloride resins. The decorative layer may further contain other layers such as a design layer, a bulk layer, and a bonding layer as optional elements. The number of layers of the decorative sheet, the type, arrangement, thickness, etc. of each layer can be appropriately selected and are not particularly limited. The adhesive layer is a layer for attaching a decorative sheet to an adherend (e.g., a molded product formed into a three-dimensional shape), and can be formed by drying the adhesive composition (e.g., after applying it to a substrate) or by crosslinking it by irradiating it with ultraviolet light, etc. EXAMPLES

[0066] Next, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to these examples. In the examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In addition, the blending amounts in the tables are parts by mass.

[0067] <Measurement of weight average molecular weight (Mw)> The Mw of the (meth)acrylic acid ester copolymer (A) was measured by the following method. The copolymer (A) dissolved in tetrahydrofuran (THF) was subjected to liquid chromatography, which separates and quantifies the copolymer based on the difference in molecular size, to identify the Mw. The measurement device used was a Shimadzu Corporation GPC LC-GPC system "Prominence" (product name). The weight average molecular weight was determined in terms of polystyrene. Four columns (product name: GMHXL, manufactured by Tosoh Corporation) and one (product name: HXL-H, manufactured by Tosoh Corporation) were connected in series, and the measurement was performed at a flow rate of 1.0 ml / min and a column temperature of 40°C.

[0068] [Production Example of (Meth)Acrylic Acid Ester Copolymer (A)] <Synthesis Example 1> Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube (hereinafter, simply referred to as the "reaction vessel"), 34 parts of 2-ethylhexyl acrylate, 3 parts of acrylic acid After charging 14 parts of ethyl, 2 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), the air in the reaction vessel was replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 17 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and then the contents of the dropping funnel were dropped over 1.5 hours while performing a polymerization reaction at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.42 million.

[0069] <Synthesis Example 2> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 63 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 27 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 950,000.

[0070] <Synthesis Example 3> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 53 parts of ethyl acetate, 10 parts of methyl ethyl ketone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 27 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 780,000.

[0071] <Synthesis Example 4> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Further, 34 parts of 2-ethylhexyl acrylate, 12.5 parts of ethyl acrylate, 3.5 parts of acrylic acid, 17 parts of acetone, 10 parts of ethyl acetate, 10 parts of 2,2'-azobisisobutyronitrile, and 10 parts of 2,2'-azobisisobutyronitrile were added to the dropping funnel. Then, 0.005 parts of aionitrile (AIBN) was charged. Next, the inside of the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.42 million.

[0072] <Synthesis Example 5> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 10 parts of ethyl acrylate, 6 parts of acrylic acid, 17 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.38 million.

[0073] <Synthesis Example 6> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 6.5 parts of ethyl acrylate, 9.5 parts of acrylic acid, 17 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.35 million.

[0074] <Synthesis Example 7> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 13.5 parts of ethyl acrylate, 2.5 parts of 2-carboxyethyl acrylate, 17 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.4 million.

[0075] <Synthesis Example 8> A reaction vessel (hereinafter sometimes simply referred to as a "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 26 parts of 2-ethylhexyl acrylate, 4 parts of n-butyl acrylate, 17 parts of ethyl acrylate, 2 parts of acrylic acid, 30 parts of acetone, 30 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and then the air in the reaction vessel was replaced with nitrogen gas. Furthermore, 27 parts of 2-ethylhexyl acrylate, 4 parts of n-butyl acrylate, 18 parts of ethyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the inside of the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) was 1.22 million.

[0076] <Synthesis Example 9> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 30 parts of 2-ethylhexyl acrylate, 17 parts of ethyl acrylate, 2 parts of acrylic acid, 30 parts of acetone, 30 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 30 parts of 2-ethylhexyl acrylate, 1 part of n-butyl acrylate, 18 parts of ethyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 12. The figure was 0 million.

[0077] <Synthesis Example 10> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 31 parts of 2-ethylhexyl acrylate, 17 parts of ethyl acrylate, 2 parts of acrylic acid, 30 parts of acetone, 30 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 31 parts of 2-ethylhexyl acrylate, 17 parts of ethyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.2 million.

[0078] <Synthesis Example 11> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 37 parts of 2-ethylhexyl acrylate, 10 parts of ethyl acrylate, 2 parts of acrylic acid, 30 parts of acetone, 30 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 38 parts of 2-ethylhexyl acrylate, 11 parts of ethyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.1 million.

[0079] <Synthesis Example 12> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 40 parts of 2-ethylhexyl acrylate, 8 parts of ethyl acrylate, 1.5 parts of acrylic acid, 30 parts of acetone, 30 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and then the air in the reaction vessel was replaced with nitrogen gas. Furthermore, 41 parts of 2-ethylhexyl acrylate, 8 parts of ethyl acrylate, 1.5 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was The mixture was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1,050,000.

[0080] <Synthesis Example 13> A reaction vessel (hereinafter sometimes simply referred to as a "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 35 parts of 2-ethylhexyl acrylate, 13.5 parts of n-butyl acrylate, 0.25 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and then the air in the reaction vessel was replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 13 parts of n-butyl acrylate, 2 parts of acrylic acid, 0.25 parts of ethyl acrylate, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the inside of the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.18 million.

[0081] <Synthesis Example 14> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 35 parts of 2-ethylhexyl acrylate, 9 parts of n-butyl acrylate, 4 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 10 parts of n-butyl acrylate, 4 parts of ethyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. was 1.25 million.

[0082] <Synthesis Example 15> A reaction vessel (hereinafter sometimes simply referred to as a "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 35 parts of 2-ethylhexyl acrylate, 8 parts of n-butyl acrylate, 6 parts of ethyl acrylate, 1.5 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 8 parts of n-butyl acrylate, 6 parts of ethyl acrylate, 1.5 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the inside of the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.28 million.

[0083] <Synthesis Example 16> Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube (hereinafter, simply referred to as the "reaction vessel"), 28 parts of 2-ethylhexyl acrylate, acrylic acid After charging 20 parts of ethyl, 1.5 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), the air in the reaction vessel was replaced with nitrogen gas. Furthermore, 22 parts of 2-ethylhexyl acrylate, 2 parts of butyl acrylate, 20 parts of ethyl acrylate, 1.5 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and then the contents of the dropping funnel were dropped over 1.5 hours while performing a polymerization reaction at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.36 million.

[0084] <Synthesis Example 17> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 27 parts of 2-ethylhexyl acrylate, 22 parts of ethyl acrylate, 1 part of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 26 parts of 2-ethylhexyl acrylate, 23 parts of ethyl acrylate, 1 part of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.37 million.

[0085] <Synthesis Example 18> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 9 parts of methyl acrylate, 4 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 35 parts of 2-ethylhexyl acrylate, 9 parts of methyl acrylate, 5 parts of ethyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.38 million. It was.

[0086] <Synthesis Example 19> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 4 parts of isobutyl acrylate, 9 parts of n-butyl acrylate, 2 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 35 parts of 2-ethylhexyl acrylate, 4 parts of isobutyl acrylate, 10 parts of n-butyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.21 million.

[0087] <Synthesis Example 20> A reaction vessel (hereinafter sometimes simply referred to as a "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 4 parts of tert-butyl acrylate, 9 parts of n-butyl acrylate, 2 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Further, 35 parts of 2-ethylhexyl acrylate, 4 parts of tert-butyl acrylate, 10 parts of n-butyl acrylate, 2 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the inside of the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.2 million.

[0088] <Synthesis Example 21> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 44 parts of 2-ethylhexyl acrylate, 6 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was replaced with nitrogen gas. Furthermore, 45 parts of 2-ethylhexyl acrylate, 5 parts of acrylic acid, 10 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and then the contents of the dropping funnel were dropped over 1.5 hours while performing a polymerization reaction at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.1 million. .

[0089] <Synthesis Example 22> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 25 parts of 2-ethylhexyl acrylate, 25 parts of ethyl acrylate, 1.5 parts of acrylic acid, 30 parts of acetone, 30 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 25 parts of 2-ethylhexyl acrylate, 22 parts of ethyl acrylate, 1.5 parts of acrylic acid, 20 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.22 million.

[0090] <Synthesis Example 23> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of n-octyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of n-octyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 17 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the dropping funnel contents were added dropwise over 1.5 hours while nitrogen was added. The polymerization reaction was carried out at reflux temperature for 5 hours under atmospheric pressure. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.49 million.

[0091] <Synthesis Example 24> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 0.4 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 3.2 parts of butyl acrylate, 14 parts of ethyl acrylate, 0.4 parts of acrylic acid, 17 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.48 million. Ta. <Synthesis Example 25> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 34 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 0.5 parts of acrylic acid, 63 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 34 parts of 2-ethylhexyl acrylate, 3 parts of butyl acrylate, 14 parts of ethyl acrylate, 0.5 parts of acrylic acid, 17 parts of acetone, 10 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.48 million.

[0092] <Comparative Synthesis Example 1> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 20 parts of 2-ethylhexyl acrylate, 25 parts of n-butyl acrylate, 4 parts of acrylic acid, 30 parts of acetone, 30 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 20 parts of 2-ethylhexyl acrylate, 26 parts of n-butyl acrylate, 5 parts of acrylic acid, 20 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1.1 million.

[0093] <Comparative Synthesis Example 2> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 42 parts of 2-ethylhexyl acrylate, 7 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 43 parts of 2-ethylhexyl acrylate, 8 parts of acrylic acid, 20 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was purged with a nitrogen atmosphere. The mixture was heated to 80°C while stirring under atmospheric conditions to initiate the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1,070,000.

[0094] <Comparative Synthesis Example 3> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 42 parts of 2-ethylhexyl acrylate, 5 parts of n-butyl acrylate, 2 parts of 2-hydroxyethyl acrylate, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 43 parts of 2-ethylhexyl acrylate, 6 parts of n-butyl acrylate, 2 parts of 2-hydroxyethyl acrylate, 20 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1,050,000.

[0095] <Comparative Synthesis Example 4> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 49 parts of 2-ethylhexyl acrylate, 0.25 parts of ethyl acrylate, 0.25 parts of acrylic acid, 60 parts of acetone, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 50 parts of 2-ethylhexyl acrylate, 0.25 parts of ethyl acrylate, 0.25 parts of acrylic acid, 20 parts of ethyl acetate, and 0.005 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 30%. The weight average molecular weight (Mw) of the acrylic polymer was 1,130,000.

[0096] Exemplary compounds are specifically shown in Table 1 below, but are not limited to these.

[0097] [Table 1]

[0098] The abbreviations in Table 1 are as follows: [Monomer (a)] 2EHA: 2-ethylhexyl acrylate NOA: n-octyl acrylate [Monomer (b)] AA: Acrylic acid BCEA: 2-Carboxyethyl acrylate [Monomer (c)] MA: Methyl acrylate EA: Ethyl acrylate [Monomer (d)] IBA: Isobutyl acrylate (Tg: 48°C) TBA: tert-butyl acrylate (Tg: 14°C) [Other monomers] BA: n-butyl acrylate HEA: 2-hydroxyethyl acrylate

[0099] Example 1 100 parts of the copolymer (Synthesis Example 1) obtained in the above Production Example was mixed with 0.05 parts (non-volatile content) of TETRAD-X (manufactured by Mitsubishi Gas Chemical Company, Inc.) as a curing agent (B), and ethyl acetate was further added as a solvent to adjust the non-volatile content to 25%, to obtain a pressure-sensitive adhesive composition of Example 1. The resulting pressure-sensitive adhesive composition was evaluated according to the measurement and evaluation methods described below.

[0100] <Preparation of decorative sheet> The obtained adhesive composition was applied to a release-treated surface of a polyethylene terephthalate (PET) film (thickness 38 μm) with one side treated for release, so that the thickness after drying would be 25 μm. Then, after drying at 105° C. for 2 minutes, the coating film was attached to a commercially available polyvinyl chloride film and aged for 7 days in an atmosphere of 23° C. and relative humidity 50% (hereinafter 50% RH) to produce a decorative sheet.

[0101] <Gel fraction> A test piece 3 mm wide and 100 mm long was cut out from the decorative sheet obtained above, and its weight was measured. The release sheet was peeled off from the test piece, and the exposed adhesive layer was attached to a 300 mesh stainless steel wire net, and the wire net was folded so that the test piece would not peel off. The test piece was wrapped in the wire net and immersed in ethyl acetate as an extraction solution and left to stand at 50°C for 24 hours. After immersion, the wire net was removed, washed with a small amount of ethyl acetate, and dried at 100°C for 30 minutes, and then its weight was measured. The gel fraction was calculated using the following formula (2). (Gel fraction)={(W2-W0-W3) / (W1-W0-W3)}×100 (Equation 2) W0: Weight of wire mesh W1: Weight of wire mesh + test piece W2: Weight of wire mesh + test specimen after drying W3: Weight of the test piece substrate

[0102] (SUS adhesion) After curing for 5 hours under an atmosphere of 23°C-50% RH, a test piece 25 mm wide and 150 mm long was cut out from the decorative sheet. The release sheet was peeled off from the cut decorative sheet, and the exposed adhesive layer was attached to the surface of a stainless steel plate (SUS304) and pressed with a 2 kg roll once. The sheet was then left for 24 hours under an atmosphere of 23°C-50% RH. Next, the adhesive strength (adhesive strength before heating) was measured using a tensile tester (Tensilon: manufactured by Orientec Co., Ltd.) in accordance with JIS Z0237, at a peel speed of 300 mm / min and a peel angle of 180°. The evaluation criteria are as follows. [Evaluation Criteria] ◎: 13N / 25mm or more, excellent. ○: 8N / 25mm or more but less than 13N / 25mm, good. △: 1N / 25mm or more but less than 8N / 25mm, usable. ×: Less than 1N / 25mm, not practical.

[0103] (PP adhesive strength) After curing for 5 hours under an atmosphere of 23°C-50% RH, a test piece with a width of 25 mm and a length of 150 mm was cut out from the decorative sheet. The release sheet was peeled off from the cut decorative sheet, and the exposed adhesive layer was attached to the surface of a polypropylene plate and pressed with a 2 kg roll once. The sheet was then left for 24 hours under an atmosphere of 23°C-50% RH. Next, the adhesive strength (adhesive strength before heating) was measured using a tensile tester (Tensilon: manufactured by Orientec Co., Ltd.) in accordance with JIS Z0237 at a peel speed of 300 mm / min and a peel angle of 180°. The evaluation criteria are as follows. [Evaluation Criteria] ◎: 8N / 25mm or more, excellent. ○: 5N / 25mm or more but less than 8N / 25mm, good. △: 1N / 25mm or more but less than 5N / 25mm, usable. ×: Less than 1N / 25mm, not practical.

[0104] (Adhesiveness to SUS curved surfaces) After curing for 5 hours in an atmosphere of 23°C and 50% RH, a test piece 25 mm wide and 150 mm long was cut out from the decorative sheet. The release sheet was peeled off from the cut decorative sheet, and the exposed adhesive layer was attached to the surface of a stainless steel (SUS304) cylinder with a diameter of 10 mm and sufficiently pressed. After that, it was left in an atmosphere of 23°C and 50% RH for 24 hours, and the peeled length of the edge was measured. The evaluation criteria are as follows. The peeled length of the edge is the sum of the peeled length of both ends, and the peeled length of one edge is the average of the peeled length of each of the left and right ends. [Evaluation Criteria] ◎: Less than 2mm, excellent. ○: 2 mm or more and less than 3 mm, good. △: Between 3mm and 5mm, usable. ×: 5mm or more, not practical.

[0105] (Polypropylene curved surface attachment) After curing for 5 hours in an atmosphere of 23°C-50% RH, a test piece 25 mm wide and 150 mm long was cut out from the decorative sheet. The release sheet was peeled off from the cut decorative sheet, and the exposed adhesive layer was attached to the surface of a polypropylene cylinder with a diameter of 10 mm and pressed firmly. After that, it was left in an atmosphere of 23°C-50% RH for 24 hours, and the length of peeling at the edge was measured. The evaluation criteria are as follows. The peeling at the edge is the sum of the peeling length at both ends, and the peeling length at one end is the average of the peeling length on each side. [Evaluation Criteria] ◎: Less than 3mm, excellent. ○: 3mm or more and less than 5mm, good. △: Between 5mm and 7mm, usable. ×: Over 7mm, not practical.

[0106] <Repositionability> The decorative sheet obtained above was evaluated for re-stickability to an acrylonitrile butadiene styrene (hereinafter referred to as ABS) resin plate when attached to the frame of a TOM molding machine (NGF molding machine, manufactured by Fuse Vacuum Co., Ltd.) based on the following evaluation criteria. (Evaluation Criteria) : No peeling marks or sounds were heard on the sample surface. Very good. ○: No peeling marks remained on the sample surface, but there was a peeling sound. Good. △: Peel marks remained partially on the sample surface. Practical use possible. ×: Peel marks remained on the entire surface of the sample. Not suitable for practical use.

[0107] <Conformity to uneven surfaces> The decorative sheet obtained above was attached to the frame of a TOM molding machine (NGF molding machine, manufactured by Fuse Vacuum Co., Ltd.), and then a melamine plate with a width of 7 cm and a length of 15 cm was set inside the frame, and a square truncated pyramid ABS resin with a top side of 20 mm, a bottom side of 40 mm, and a height of 20 mm was set on top of the melamine plate. The melamine plate and the ABS resin were then molded so as to cover them with the decorative sheet, to obtain a decorative structure. The surface condition after molding was evaluated based on the following evaluation criteria. (Evaluation Criteria) ◎: No lifting or peeling is observed on any surface. Very good. ○: No lifting is observed on the uneven surface, but some peeling occurs at the edge. △: Some lifting was observed on uneven surfaces, and peeling occurred at the edges. Practical use is possible. ×: Lifting occurred on all uneven surfaces, and peeling occurred on the entire surface. Not practical.

[0108] <Durability after molding> The decorative sheet obtained above was attached to the frame of a TOM molding machine (NGF molding machine, manufactured by Fuse Vacuum Co., Ltd.), and then an ABS resin plate measuring 10 cm x 7 cm x 5 mm thick was set inside the frame. The ABS resin plate was then covered with the decorative sheet and molded at 130°C to obtain a decorated structure. The molded product obtained was then left for 24 hours in a 23°C-50% RH atmosphere, after which a 5 cm long cross was made on the surface of the molded product, and the product was left for 168 hours in a high temperature or high temperature and high humidity environment (80°C / 90°C / 80°C-95% RH), after which it was evaluated for lifting and displacement based on the following evaluation criteria. (Evaluation Criteria) ◎: No lifting or peeling, but some misalignment of less than 1 mm occurred. Very good. ○: No lifting or peeling, but misalignment of 1 mm or more and less than 3 mm occurred. Good. △: No lifting or peeling, but misalignment of 3 mm to less than 10 mm occurred. Usable. ×: Lifting or peeling occurs. Not practical.

[0109] (Examples 2 to 34, Comparative Examples 1 to 4) The adhesive compositions and decorative sheets of Examples 2 to 34 and Comparative Examples 1 to 4 were obtained in the same manner as in Example 1, except that the types and amounts of the (meth)acrylic acid ester copolymer (A) and the curing agent (B) and additives contained in the adhesive composition were changed to those shown in Table 2. The exemplified compounds are specifically shown in Table 2, but are not limited to these. The evaluation results of the obtained decorative sheets of Examples 2 to 34 and Comparative Examples 1 to 4 are shown in Table 3.

[0110] [Table 2]

[0111] [Table 3]

[0112] The abbreviations in Table 2 are as follows: [Hardening agent (B)] TETRAD-X: Epoxy curing agent (Mitsubishi Gas Chemical Company, Inc., N,N,N',N'-tetraglycidyl-m-xylylenediamine) AL: Metal chelate curing agent (Kawaken Fine Chemicals, aluminum trisacetylacetonate) TDI-TMP: Isocyanate-based hardener, trimethylolpropane adduct of tolylene diisocyanate [Additives] AcAc: Acetylacetone

[0113] The present invention is not limited to the above-described embodiment and examples, and appropriate design changes are possible without departing from the spirit of the present invention.

[0114] The adhesive composition for decorative sheets of the present invention was excellent in adhesive strength, curved surface attachment property, reattachment property, unevenness-following property, and durability under high temperature or high temperature and high humidity environment, as shown in Examples 1 to 34 in Table 3. In contrast, Comparative Examples 1 to 4 in Table 3 were found to be inferior in the above-mentioned physical properties. The composition having the above-mentioned excellent properties can be suitably used for decoration of, for example, aircraft, automobiles, railways, interior and exterior building materials, nursing and medical fields, electrical appliances, etc., and its use is not particularly limited, but it is preferably used for automobile interior and exterior parts, home appliances, smartphones, and housing building materials, more preferably used for automobile interior and exterior parts and housing building materials, and particularly preferably used for automobile interior and exterior parts. In addition, as a method for decoration using a decorative sheet, insert molding method, in-mold molding method, vacuum molding method, vacuum pressure molding method, etc. are known, and although it is not particularly limited, the method using vacuum molding method and vacuum pressure molding method is particularly preferred.

Claims

1. Contains a (meth)acrylic acid ester copolymer (A) and a curing agent (B), The (meth)acrylic acid ester copolymer (A) is a copolymer of a monomer mixture, The monomer mixture contains (a) an alkyl (meth)acrylate monomer having an alkyl group with 8 carbon atoms and (b) a monomer having a carboxy group, the content of the (meth)acrylic acid alkyl ester monomer (a) having an alkyl group with 8 carbon atoms is 50 to 98 mass% in 100 mass% of the monomer mixture; The content of the monomer (b) having a carboxy group is more than 0 mass% and less than 12 mass% in 100 mass% of the monomer mixture. A pressure-sensitive adhesive composition for decorative sheets used for attachment to an adherend by vacuum forming or vacuum / pressure forming.

2. The adhesive composition for decorative sheets according to claim 1 , wherein the curing agent (B) is an epoxy-based curing agent.

3. The adhesive composition for decorative sheets according to claim 1, characterized in that the monomer mixture further contains at least one of (c) an alkyl (meth)acrylate ester monomer having 1 to 3 carbon atoms in the alkyl group and (d) an alkyl (meth)acrylate ester monomer having a homopolymer glass transition temperature of -30°C or higher and having 4 carbon atoms in the alkyl group, the total content of which is 1 to 45 mass% in 100 mass% of the monomer mixture.

4. A decorative sheet comprising a substrate and an adhesive layer made of the adhesive composition for decorative sheets according to any one of claims 1 to 3.

5. A decorative structure comprising an adherend and the decorative sheet according to claim 4.

6. The method for producing a decorative structure according to claim 5, wherein the decorative sheet is integrated with an adherend by vacuum forming or vacuum / pressure forming to form the decorative structure.

Citation Information

Patent Citations

  • Adhesive film, production method of shaped body using the same, and shaped body obtained thereby

    JP2009035588A

  • Film for decorative molding and decorative molded article

    JP2017132205A

  • Adhesive composition for decorative film

    WO2021049480A1